2013
DOI: 10.1016/j.exppara.2012.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Ocular experimental leishmaniasis in C57BL/10 and BALB/c mice induced by Leishmania amazonensis infection

Abstract: There are few studies on human ocular leishmaniasis found in the literature. The purpose of this study was to describe experimental ocular leishmaniasis, caused by Leishmania amazonensis evaluating two different infection routes: intravitreal and instillation in C57BL/10 and BALB/c mice. In this work all animals presented low anti-Leishmania IgM and IgG titers regardless of the infection route or mouse strain. The histopathological eye analysis showed that the mice inoculated by the intravitreal route develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…It was possible to identify and characterize by ultrasonography the following pathologies: lens rupture, lens dislocation, retinal detachment and cataract. Calabrese et al [4] evaluated ocular changes in mice experimentally infected with Leishmania amazonensis and found that ocular lesions may be associated with the deposition of immunoglobulins in response to type III hypersensitivity stimulated by the presence of parasite antigens. This accumulation of immunocomplexes favors the appearance of ocular lesions.…”
Section: Discussionmentioning
confidence: 99%
“…It was possible to identify and characterize by ultrasonography the following pathologies: lens rupture, lens dislocation, retinal detachment and cataract. Calabrese et al [4] evaluated ocular changes in mice experimentally infected with Leishmania amazonensis and found that ocular lesions may be associated with the deposition of immunoglobulins in response to type III hypersensitivity stimulated by the presence of parasite antigens. This accumulation of immunocomplexes favors the appearance of ocular lesions.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, BALB/c mice infected via the instillation route presented no lesions but an enhancement of intact MCs in the conjunctival region at 30 days p.i., and a discreet inflammatory infiltrate and degranulated MCs were observed in the conjunctival region at 60 days p.i. (32). …”
Section: Mcs In Leishmania Spp Infectionmentioning
confidence: 99%
“…Literatürde göz ve çevresinin değerlendirildiği birkaç çalışmada tutulum oranı %2-5 olarak rapor edilmiştir 10,[13][14][15] . Durdu ve ark.…”
unclassified